Implementation of The Values of Religious Moderation and Morals in Extracurricular Learning of Ratoh Jaroe Dance Cultural Arts - Isninda Nur Masithoh (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
This research aims to describe a implementation the value of religious moderation and morals in extracurricular Learning of Ratoh Jaroe dance cultural arts and the impact of these Learning on students. This research uses qualitative type. They are located at 1 st senior high school Batik Surakarta under auspices of the art institute SANSA. The subject in this study is a dance coach / Arts Teacher in that School and for collecting data by way of observation, interview and documentation. And to test the reliability of the data using the triangulation of the source. Then it was analyzed by interactive model: data collection, data presentation, and conclusion. The implementation of tolerance in the extracurricular learning of this dance is meant that in this cultural art there are no restrictions on differences in religion, race or ethnicity. All members unite to carry out this dance even though they are different in terms of religion even the nature and characteristics of this dance are very leaning towards islam, but for students of other religions participate in carrying it out. The efforts to apply moral values in extracurricular learning by implementing a disciplinary, unity and cooperation, and maintaining self respect. Tolerance and morals values in this dance is also seen in the cohesiveness together, no one is superior to oneself all in rhythm and compact in the harmony of songs and movements, this activity affects students attitudes towards tolerance and respect for other cultures. This extracurricular learning can instill noble cultural values in student through the association of role models and invitations to practice these values. This attitude can be seen when learning in the classroom or in the school environment and can even be a role model for other students. This is in accordance with the objectives of extracurricular which are expected to be activities to support skills, self development, and students characteristics.